The Role Of A Number Of Organizational Variables In The Feeling Of Career Alienation Among Managers And Executives In The Presidency Of The Municipality Of Duhok - Othman, Hilovan H. (Academic Journal of Nawroz University, 2017)
This research aims at identifying the effect of organizational variables on the sense of expatriation of employees in the municipality of Duhok. The research problem in the main question was whether the organizational variables have an effect in raising the sense of functional alienation in the research sample. The researcher adopted the test of the organizational variables as an independent variable, which is (work systems and procedures, centralization, organizational structure, motivation and incentives, career rotation) Career as a supported variable. Two basic research hypotheses were formulated. 1. There are significant positive correlation between the organizational variables as a complete independent variable and the functional expatriation as a total dependent variable. There is a significant relationship of organizational variables as a total independent variable in functional expatriation as a total dependent variable. The research will depend on the questionnaire as a key tool for field data collection, using a number of statistical methods in data analysis. The most important results of the research were the understanding of the studied sample of both the concept of organizational variables and functional expatriation and their observation during the job performance. It is concluded from the statistical analysis that there is a strong correlation and effect between organizational variables and functional expatriation. In light of these conclusions, the study described a number of proposals that serve the field in question. Perhaps the most important of these is the need for senior management to be close to the employees and to create an atmosphere conducive to the participation of the staff in decision-making and the determination of public policies, in addition to achieving justice through the distribution of motives and incentives, For all employees equally.